Green Budgeting and the Quality of Local Government Financial Reports: An Empirical Study on the Government of Surabaya City - Ulfa, Wia; Rany, Syarifah Shantia; Meutia, Rita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the effect of green budgeting implementation on the quality of local government financial statements, with empirical evidence from the Surabaya City Government. Green budgeting is an innovative accounting approach that integrates environmental considerations into fiscal planning, thereby enhancing transparency, accountability, and long-term fiscal sustainability. The research applies a quantitative method by utilizing data from financial reports, budget documents, and supporting interviews. Linear regression analysis is employed to test the relationship between green budgeting and financial reporting quality. The findings demonstrate that green budgeting has a significant positive impact on the quality of local government financial statements, particularly in improving transparency and accountability in financial disclosure. This study contributes to the body of knowledge in public sector accounting by providing evidence on the role of environmentally oriented budgeting in strengthening financial governance. Furthermore, the results offer practical implications for policymakers, suggesting that the adoption of green budgeting can serve as a strategic tool for local governments to align fiscal practices with sustainable development goals (SDGs).